Vladimir Akimovich Filipenko - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The article is devoted to the jubilee of the honored worker of science and technology of Ukraine, the head of the Joint Pathology Department of Sytenko Institute of Spine and Joint Pathology of the NAMS of Ukraine , Doctor of Medical Sciences, Professor V.A. Filipenko.